2020
DOI: 10.15252/msb.20199146
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian gene expression variability is explained by underlying cell state

Abstract: Gene expression variability in mammalian systems plays an important role in physiological and pathophysiological conditions. This variability can come from differential regulation related to cell state (extrinsic) and allele‐specific transcriptional bursting (intrinsic). Yet, the relative contribution of these two distinct sources is unknown. Here, we exploit the qualitative difference in the patterns of covariance between these two sources to quantify their relative contributions to expression variance in mam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 99 publications
1
87
1
Order By: Relevance
“…Even for single‐cell experiments, which can control for genetic and macro‐environmental factors, there is ongoing debate as to whether the observed gene‐specific expression variation can be explained by intrinsic (e.g. transcription bursting) or extrinsic (cell‐to‐cell variability) factors (Battich et al , ; Larsson et al , ; Foreman & Wollman, ), or whether these sources are indistinguishable (Eling et al , ). Yet, despite the differences in interpretation of the underlying sources of variation, there is a consensus that genes differ in their expression variation.…”
Section: Discussionmentioning
confidence: 99%
“…Even for single‐cell experiments, which can control for genetic and macro‐environmental factors, there is ongoing debate as to whether the observed gene‐specific expression variation can be explained by intrinsic (e.g. transcription bursting) or extrinsic (cell‐to‐cell variability) factors (Battich et al , ; Larsson et al , ; Foreman & Wollman, ), or whether these sources are indistinguishable (Eling et al , ). Yet, despite the differences in interpretation of the underlying sources of variation, there is a consensus that genes differ in their expression variation.…”
Section: Discussionmentioning
confidence: 99%
“…Given that previous studies identified cell size as a source of extrinsic variability in transcript counts [26,27,29,35], we quantified cell sizes and found a positive correlation with mRNA number for all genes (Supp figure 2). In fact, we found a linear relationship between the log area and the log mean mRNA number, indicating a power-law scaling (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The extrinsic sources of noise in our model, which include area and variable burst size, had a weaker contribution for all three clock genes. Previous studies have shown that the relative proportions of intrinsic versus extrinsic noise is both condition-(cell types, cell states) and gene-specific, and regression models that use cellular features as explanatory variables can account for between 10-80% of the variance, depending on the gene [26,27]. In the cells used here, the strong influence of transcriptional bursting and dominance of intrinsic noise is consistent with live imaging of a Bmal1 transcriptional reporter in the same cell line under similar growth conditions, where intrinsic noise was estimated to be 4-times larger than extrinsic noise [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] There is also evidence that after controlling for cell cycle and cell state, the remaining fluctuations are solely due to biochemical reaction noise. 8,9 Recent studies have demonstrated that variability is conferred from mother to siblings cells, 5 inheritable fluctuations in gene expression found within clonal cancer cell lines may lead to drug resistance, 6 and distributions in the number of mitochondria can explain cell death due to TNF-related apoptosis. 7 Regardless of the underlying mechanism, cell to cell variability has broad implications outside of studying mechanisms heterogeneity in clonal cell lines and drug resistance in cancer.…”
Section: Introductionmentioning
confidence: 99%